GM-018 Improvement plan for daa prescription compliance in the pitiÉ-salpÊtriÈre hospital. (14th February 2016) - Davies, SE Campbell; Liou, A; Ngo, KTA; Poynard, T; Tilleul, P; Fievet, MH
Abstract : Background: Since the beginning of 2014, an increasing number of direct acting antiviral agents (DAAs) have been approved in France for treating chronic hepatitis C virus (HCV). In order to achieve high quality treatment with these costly drugs, multidisciplinary treatment planning meetings (RCP) between clinicians and pharmacists take place periodically. The final team decision is a mandatory requisite for DAA prescription which is also subject to strict reimbursement rules. Audits of DAA prescriptions were performed by pharmacists to detect non-conformities before and after an improvement plan (IP) hospital meeting on 1 June 2015. Purpose: To assess the impact of the IP in prescribing DAAs. Material and methods: DAA prescriptions were collected from hospital dispensing software. A data collection audit form was designed containing data about the prescriber and patient, the prescription and RCP decision compliance. Results: 244 prescriptions were audited (108 for April 2015; 136 for July 2015). In both audits all prescriptions contained at least one error. The main non-conformities detected were: 25% non-authorised prescribers, missing data (13% prescriber identification number, 20% patient's birth date, 10% international non-proprietary name, 44% length of treatment in weeks rather than in months). The RCP date was reported in only 18% of cases, but only 10% of prescriptions were identified as non-compliant with the RCP decision (9 cases wrong prescribed drug, 2 cases no RCP decision). In the second audit, important improvements were observed for: percentage of authorised prescribers (90%), reported prescriber identification number (54%) and RCP date (35%). 7 prescription deviations from the official RCP decision (5%) were found: type of prescribed drug (3 cases), treatment duration (3 cases) and no RCP decision (1 case). Weak improvements were reported for patient's birth date (22%) and length of treatment in weeks (49%). Conclusion: In conclusion, the IP meeting was successful, showing that internal audits are effective instruments in identifying weaknesses in the system and in measuring corrective actions. The pharmacist, as an integral member of the multidisciplinary team, has an essential role in guaranteeing the actual application of the RCP decision in order to obtain the best patient outcomes. No conflict of interest.